Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Certainly! Let's address the transformation of the given function [tex]\( y = x^2 \)[/tex]:
1. Reflected across the x-axis:
To reflect [tex]\( y = x^2 \)[/tex] across the x-axis, we multiply the function by [tex]\(-1\)[/tex]. Therefore, the reflection of [tex]\( y = x^2 \)[/tex] across the x-axis is:
[tex]\[ y = -x^2 \][/tex]
2. Shifted right 3 units:
To shift any function [tex]\( y = f(x) \)[/tex] to the right by 3 units, we replace [tex]\( x \)[/tex] with [tex]\( x - 3 \)[/tex] in the function. Let’s apply this to our reflected function [tex]\( y = -x^2 \)[/tex]:
[tex]\[ y = -(x - 3)^2 \][/tex]
3. Shifted up 6 units:
To shift any function [tex]\( y = f(x) \)[/tex] up by 6 units, we add 6 to the function. Applying this to the function [tex]\( y = -(x - 3)^2 \)[/tex]:
[tex]\[ y = -(x - 3)^2 + 6 \][/tex]
Therefore, the equation for the function that has the graph with the shape of [tex]\( y = x^2 \)[/tex], but reflected across the x-axis, shifted right by 3 units, and shifted up by 6 units is:
[tex]\[ y = -(x - 3)^2 + 6 \][/tex]
1. Reflected across the x-axis:
To reflect [tex]\( y = x^2 \)[/tex] across the x-axis, we multiply the function by [tex]\(-1\)[/tex]. Therefore, the reflection of [tex]\( y = x^2 \)[/tex] across the x-axis is:
[tex]\[ y = -x^2 \][/tex]
2. Shifted right 3 units:
To shift any function [tex]\( y = f(x) \)[/tex] to the right by 3 units, we replace [tex]\( x \)[/tex] with [tex]\( x - 3 \)[/tex] in the function. Let’s apply this to our reflected function [tex]\( y = -x^2 \)[/tex]:
[tex]\[ y = -(x - 3)^2 \][/tex]
3. Shifted up 6 units:
To shift any function [tex]\( y = f(x) \)[/tex] up by 6 units, we add 6 to the function. Applying this to the function [tex]\( y = -(x - 3)^2 \)[/tex]:
[tex]\[ y = -(x - 3)^2 + 6 \][/tex]
Therefore, the equation for the function that has the graph with the shape of [tex]\( y = x^2 \)[/tex], but reflected across the x-axis, shifted right by 3 units, and shifted up by 6 units is:
[tex]\[ y = -(x - 3)^2 + 6 \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.